An ANMS‐NASPGHAN consensus document on anorectal and colonic manometry in children. Issue 1 (9th October 2016) - Rodriguez, L.; Sood, M.; Di Lorenzo, C.; Saps, M.
Abstract: Background: Over the last few years, the study of the colon and anorectal function has experienced great technical advances that have facilitated the performance of the tests and have allowed a more detailed characterization of reflexes and motor patterns. As a result, we have achieved a much better understanding of the pathophysiology of children with defecation problems. Anorectal and colonic manometry are now commonly used in all major pediatric referral centers as diagnostic tools and to guide the management of children with intractable constipation and fecal incontinence, particularly when a surgical intervention is being considered. Purpose: This review highlights some of the recent advances in pediatric colon and anorectal motility testing including indications and preparation for the studies, and how to perform and interpret the tests. This update has been endorsed by the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN). Abstract : The study of the colon and anorectal function has experienced great technical advances that facilitated the performance of tests and allowed a more detailed characterization of reflexes and motor patterns. As a result, we have achieved a much better understanding of the pathophysiology of children with defecation problems. This review highlights some of the recent advances in pediatric colonic and anorectal motility testing including indications and preparation and how to interpret the results.